O ensino-aprendizagem do gênero resenha crítica na universidade - Cervera, Maria Christina da Silva Firmino (2008)
Reading comprehension and textual production (writing) teaching in the mother language has been focus of many academic researches (Machado & Cristóvão, 2006; Machado, 2004; Muniz-Oliveira, 2005; Souza, 2003 and many others) that reveal their importance to a more productive learning process. Studies about specific didactic sequences for each genre and each production situation, more specifically the academic one, has also brought us important contributions to the teaching and language studies area (Machado, Lousada & Abreu-Tardelli, 2004a, 2004b, for example). At this context, the objective of this research is to analyze a didactic sequence of the critical review genre written by me (inspired from Machado, Lousada & Abreu-Tardelli, 2004a) and applied to college students from the night first semester at a private superior teaching institution from São Paulo, from the results got for them at this process. The justification for this search starts from the assumption that an appropriate educational material, based on the development of didactic sequences, for teaching a particular genre, could be an important tool in the field of production of this genre in particular, what can be valuable to a public that starts the graduation without having the control about the field on the academic genres production. Besides, my choice for the focus on the critical review teaching occurred because this genre also presupposes the development of reading skills, (although this will not be the object of this research) requiring that we students discoursive operations from the order of describing, assessing and interpreting as well (Beacco & Darot, 1984, as resumed by Machado, 1996: 142), very requested in texts of different genres in higher education. The theoretical and methodological basis for this research is the Sociodiscoursive Interactionism - ISD - (Bronckart, 1997/2003; 2004, 2006, among others), which say that the primary function of language is the textual genres appropriateness which circulate in a given society and this is a basic condition for the development of the language skills of the users of a language. To establish a didactic sequence, I was based in Dolz & Schneuwly (1998) works and specially to treat about the critical review genre, I was based in Machado, Lousada and Abreu-Tardelli (2004a) and other works produced by Machado in this area as well. The results show that to work the production of academic critical reviews from a didactic sequence can offer to the students opportunities for reflecting and appropriating of such a genre. However, so that the work can be more effective, the didactic sequence developed and applied at this search requires adjustments in some aspects, particularly about those commented at the end of the dissertation